Functional liposome loaded curcumin for the treatment of Streptococcus mutans biofilm - Hu, Zhimin; Tang, Ying; Jiang, Bulin; Xu, Yue; Liu, Siying; Huang, Cui (Frontiers in Chemistry, 2023)
Plaque biofilms, mainly formed by Streptococcus mutans (S. mutans), play an important role in the occurrence and development of dental caries. Antibiotic treatment is the traditional way to control plaque. However, problems such as poor drug penetration and antibiotic resistance have encouraged the search for alternative strategies. Our research group has been committed to the application of plant extracts in oral diseases for a long time. In this paper, we hope to avoid antibiotic resistance through the antibacterial effect of curcumin, a natural plant extract with photodynamic effects, on S. mutans. However, the clinical application of curcumin is limited due to its low water solubility, poor stability, high metabolic rate, fast clearance rate, and limited bioavailability. At present, there are few studies on the delivery of curcumin to S. mutans biofilm. Therefore, we constructed a curcumin-loaded liposome (Cur@LP) that can adhere to the surface of S. mutans biofilm, aiming to deliver curcumin into the biofilm and disperse it. We characterized the morphology, particle size, and zeta potential of liposomes. We evaluated the adhesion and antibacterial effect of Cur@LP on S. mutans biofilm. The results of the confocal laser scanning microscope showed that Cur@LP effectively adhered to the S. mutans biofilm and inhibited the growth of it. This biofilm removal strategy has the potential to be translated into the clinic.